A survey to evaluate diversity, equity and inclusion in large collaborations - van Scherpenberg, Juliane; Heckmann, Lea; Strišković, Jelena; Berti, Alessio; Dorner, Daniela; Elsaesser, Dominik; Green Jarred Gershon; Manganaro, Marina; Satalecka, Konstancja; MAGIC collaboration (Italy, 2025)
In 2020, the MAGIC collaboration started an initiative to improve diversity, equity and inclusion (DEI) in the collaboration. One of the major actions undertaken by this initiative was a survey which was distributed among all MAGIC members with the goal of getting a clear picture of the status quo and to identify potential problems or opportunities concerning DEI related topics.
Two surveys have since been performed - one in December 2020 and one in June 2022 - covering questions related to demographics, working conditions, recognition, harassment, bullying and discrimination. In this contribution, we present the questionnaire and strategy used to run these surveys. Additionally, we describe the impact the survey had within the collaboration and which actions have been taken as a direct consequence of the survey results.